Pengaruh Economic Value Added , Market Value Added, dan Kebijakan Dividen terhadap Nilai Perusahan - Azizah, Fara; Sulistyowati, Erna (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: The current study aims to envestigate the influence of Economic Value Added (EVA), Market Value Added (MVA), and dividend policy on the value of enterprises classified as LQ45 that were publicly listed on the Indonesia Stock Exchange from 2020 to 2022. The study encompasses a dependent variable, Firm Value, alongside independent variables comprising Economic Value Added (EVA), Market Value Added (MVA), and dividend policy. Methodology: Quantitative research is what this study is all about. Information gathered from stock prices and yearly reports utilizing documentation methodologies. Twenty businesses were chosen the Purposive Sampling technique. Multiple Linear Regression in SPSS Version 27 was employed to examine in data. Results: Findings demonstrated that EVA has no influence on company value, but MVA has a large positive effect on firm value, and dividend policy has a massive positive effect on firm value. Meanwhile, the EVA, MVA, and Dividend Policy have a major beneficial influence on the firm’s worth. Limitations: One of its drawbacks is the limited three-year analysis time; perhaps, future researchers will be able to employ a longer study period. Contribution: The study’s findings may help businesses and investors weigh EVA, MVA and dividend policy factors when making choices.